The studies of a new ceramic composite — (Zr0.92Y0.08)O1.96 dispersed lanthanum titanium aluminium oxide. (1st April 2016) - Zhang, Peng; Choy, Kwang-leong
Abstract: A new ceramic composite (Zr0.92 Y0.08 )O1.96 dispersed in LaTi2 Al9 O19 as a thermal barrier material was synthesized by the hybrid sol–gel method. The composite ceramic has good thermochemical stability up to 1500 °C. The thermal conductivity of composite ceramic is circa. 1.0 W/m·K at ambient temperature and the coefficients of thermal expansion are very stable and comparable to (Zr0.92 Y0.08 )O1.96 about 10.7 × 10 − 6 K − 1 at 1223 K. The sintering resistance and mechanical properties become better after being dispersed. Therefore, the new ceramic composite synthesized by hybrid sol–gel method can be a promising candidate as a thermal barrier material on Ni-based superalloy. Graphical abstract: Highlights: New composite 4 mol% yttria stabilized zirconia (4YSZ) dispersed LaTi2 Al9 O19 (LTA) is synthesized by a hybrid sol-gel method. The new ceramic composite shows good thermochemical stability up to 1500 o C. The thermal conductivity of the new ceramic composite is lower than each component at ambient temperature. The coefficient of thermal expansion of 4YSZ dispersed in LTA (LTA-4YSZ) is comparable to 4YSZ. Compared with LTA and 4YSZ, LTA-4YSZ has the best sintering resistance. The Young's Modulus of LTA-4YSZ composite becomes lower while the hardness becomes higher.